2019
DOI: 10.4018/jgim.2019100106
|View full text |Cite
|
Sign up to set email alerts
|

Asia-Pacific Students' Awareness and Behaviour Regarding Social Networking in the Education Sector

Abstract: Social networking (SN) technology has been presented to human beings as a means of communicating, collaborating, connecting, and cooperating to exchange knowledge, skills, news, chat, and to maintain contact with peers world-wide. This article examines SN awareness in the Asia-Pacific (AP) education sector (ES) with a specific focus on the advantages and disadvantages of SN; and investigated whether AP culture influences SN adoption by the ES. An online survey was distributed to 1014 AP students and a total of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 72 publications
(15 reference statements)
0
6
0
Order By: Relevance
“…Studies have shown that when staff use a social network to share knowledge within their organisation, it is crucial that they utilise it correctly in order to maximise the benefit and help generate new knowledge [ 25 ]. Yu and Yu [ 26 ] explain that the more individuals use social network for knowledge sharing within their workplace, the greater their contributions are to the organisation as they can more effectively exchange valuable information and knowledge among their peers.…”
Section: Background: Knowledge Sharing Information and Privacymentioning
confidence: 99%
“…Studies have shown that when staff use a social network to share knowledge within their organisation, it is crucial that they utilise it correctly in order to maximise the benefit and help generate new knowledge [ 25 ]. Yu and Yu [ 26 ] explain that the more individuals use social network for knowledge sharing within their workplace, the greater their contributions are to the organisation as they can more effectively exchange valuable information and knowledge among their peers.…”
Section: Background: Knowledge Sharing Information and Privacymentioning
confidence: 99%
“…Table 1 shows the benefits and risks associated with SN according to the literature ( Al-Oqily and Alkhatib, 2016 ; Alqahtani, 2016 ; Benn et al., 2008 ; Fitzpatrick, 2010 ; Goktalay and Ozdilek, 2016 ; Issa et al., 2019 ; Jeri-Yabar et al., 2019 ; Kemp, 2015 ; Kimmons et al., 2017 ; Lalonde and Castro, 2015 ; Malak et al., 2017 ; Mccarroll and Curran, 2013 ; Sonnenwald and Pierce, 2000 ; Yadav et al., 2020 ; Zygmunt et al., 2020 ). These benefits include: the acquisition of cutting-edge knowledge, increased collaboration, independent learning, improved communication skills, increased awareness of environmentally friendly practices (i.e., be more sustainable people, provide reliable and scalable services, become “greener” in their activities, and reduce the carbon footprint) and the opportunity to make new acquaintances (i.e., friendships, romance, and work).…”
Section: Related Workmentioning
confidence: 99%
“…However, the implementation of SN in the higher education sector can give rise to several risks or disadvantages regarding students’ cognitive, social, and physical development, and their security and privacy. Table 1 shows the SN risks in detail based on the current literature ( Al-Oqily and Alkhatib, 2016 ; Almufaraj and Issa, 2018 ; Alqahtani, 2016 ; Alqahtani and Issa, 2018 ; Chakraborty et al., 2016 ; Goktalay and Ozdilek, 2016 ; Issa et al., 2014 , 2016a , 2019 ; Jeri-Yabar et al., 2019 ; Kircaburun, 2016 ; Krouska et al., 2019 ; Peris et al., 2020 ; Samad et al., 2019 ; Shi et al., 2018 ; Symons et al., 2020 ; Vernon et al., 2017 ; Woods and Scott, 2016 ).…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Modern education theory believes that physical education is a systematic, planned, and purposeful information conversion process, and the teaching process is regarded as a dynamic process of information extraction and feedback. Therefore, the management of physical education is essentially a kind of information management [7][8]. In addition to managing different types of information in physical education, such as "course selection, course evaluation, physical education curriculum resources," an information management system for physical education can also be made to enhance the quality of information management and contribute positively to physical education.…”
Section: Introductionmentioning
confidence: 99%